Efficient screening of pancreatic lipase inhibitors from cod meat hydrolysate through ligand fishing strategy - Tian, Yongqi; Liu, Cuicui; Wang, Shaoyun; Du, Ming; Zhu, Beiwei (Frontiers in Nutrition, 2022)
Obesity has become an increasingly serious public health problem. Pancreatic lipase (PL) is identified as a ideal target for the prevention and treatment of obesity. Orlistat, the only approved PL inhibitor (PLI), is a powerful weight loss drug but has many side effects. Therefore, there is an urgent need to discover powerful PLIs with high safety. Protein hydrolysate has been demonstrated to be a treasure trove of PLIs, but recognizing responsible functional peptides from them is like looking for a needle in a haystack. In this work, we synthesized and optimized a PL ligand fishing model (PLLFM) using magnetic nanoparticles (MNPs), then PLLFM was used to quickly fish out potential PLIs from the Cod meat hydrolysate (CMH). Finally, two new PLIs, GSPPPSG and KLEGDLK were identified with IC50 of 0.60 and 1.08 mg/mL, respectively. The Lineweaver-Burk diagram showed that GSPPPSG is a non-competitively dominant mixed-type PLI, whereas KLEGDLK is a competitive inhibitory-type PLI. Moreover, molecular docking suggested that both peptides can stably bind to the key amino acid residues of the PL active site, mainly through hydrogen bonding, hydrophobic, and electrostatic interactions. In general, we not only established a method to rapidly fish out potential PLIs from protein hydrolysate, but also provided safe and efficient lead compounds for the development of novel diet foods or drugs.